Determinants of Creativity in Marketing - Garbarski , Lechosław (Studia Oeconomica Posnaniensia, 2018)
The rapid changes of economic activity determinants require innovative solutions. Creativity is the basis of these solutions. Creativity is related to divergent thinking and could be analyzed at three levels. Two of them - the individual and macro level are described in this article. Many factors which enable or restrict creative thinking were identified. Also methods of increasing creativity were analyzed.